Synovial Fluid of Patient With Rheumatoid Arthritis Enhanced Osmotic Sensitivity Through the Cytotoxic Edema Module in Synoviocytes - Ji, Min Jeong; Ryu, Hee Jung; Hong, Jeong Hee (Frontiers in Cell and Developmental Biology, 2021)
Rheumatoid arthritis (RA) is an autoimmune disease that causes inflammation of the synovial membrane ultimately leading to permanent damage in the affected joints. For this study, synovial fluids from 16 patients diagnosed with either RA or osteoarthritis (OA) were used to examine volume regulation and cooperative water channels, both of which are involved in the cytotoxic edema identified in RA-fibroblast-like synoviocytes (FLS). The osmolarity and inflammatory cytokine interleukin (IL)-6 of synovial fluids from RA patients were mildly enhanced compared to that from OA patients. RA-FLS demonstrated the enhanced property of regulatory volume increase in response to IL-6 and synovial fluids from RA patients. Although there was no difference in the protein expression of the volume-associated protein sodium–potassium–chloride cotransporter1 (NKCC1), its activity was increased by treatment with IL-6. Membrane localization of NKCC1 was also increased by IL-6 treatment. Additionally, both the protein and membrane expressions of aquaporin-1 were increased in RA-FLS by IL-6 stimulation. The IL-6-mediated enhanced osmotic sensitivity of RA-FLS likely involves NKCC1 and aquaporin-1, which mainly constitute the volume-associated ion transporter and water channel elements. These results suggest that RA-FLS provide enhanced electrolytes and concomitant water movement through NKCC1 and aquaporin-1, thereby inducing cellular swelling ultimately resulting in cytotoxic edema. Attenuation of cytotoxic edema and verification of its related mechanism will provide novel therapeutic approaches to RA treatment within the scope of cytotoxic edema.